Analysis on Differential Protection Sensitivity of Traction Transformers Based on Different Conversion Modes. Issue 1 (December 2020) - Xiaobao, Liu; Yuping, Zheng; feng, Long; Tonghua, Wu; Shuyan, Pan; Lin, An
Abstract: With the rapid development of high-speed rail technology in China, the traction transformers of various types have been used more and more extensively. The differential protection of traction transformers has different differential conversion modes [1-2] which are different in their sensitivities. In this paper, taking the YNV traction transformer as an example, by comparing the sensitivities of two different common differential conversion modes and through analysis, it shows that the sensitivities of differential protection are slightly different. The sensitivities of differential protections based on different principles depend on the retention degree of differential current to the positive sequence, negative sequence and zero sequence components in the internal fault current. The sensitivity of phase current minus zero sequence differential is the highest when single-phase grounded, which completely retains all the sequence components in the internal fault current. The sensitivity of interphase differential protection is the highest when interphase fault occurs. The widely used phase current differential and phase current minus zero sequence differential do not reflect the zero-sequence component of internal fault current, which provides the basis for field fault analysis and setting.